Practical correlation bias correction in two-way fixed effects linear regression - Simen Gaure (University of Oslo, Department of Economics, 2014)
When doing two-way fixed effects OLS estimations, both the variances and covariance of the fixed effects are biased. A formula for a bias correction is known, but in large datasets it involves inverses of impractically large matrices. We detail how to compute the bias correction in this case.
Keywords: C13; C33; C55; C87; 330; Limited mobility bias; Two way fixed effects; Linear regression